Adequate intake of potassium does not cause hyperkalemia in hypertensive individuals taking medications that antagonize the renin angiotensin aldosterone system. Issue 4 (31st August 2016) - Malta, Daniela; Arcand, JoAnne; Ravindran, Anju; Floras, Vanessa; Allard, Johane P; Newton, Gary E
ABSTRACT: Background: Reduced potassium excretion caused by angiotensin-converting enzyme inhibitors (ACEis) and angiotensin receptor blockers (ARBs) may increase the risk of hyperkalemia (serum potassium concentration >5 mmol/L) in the setting of increased potassium intake. Objective: The purpose of this study was to assess the effect of increasing dietary potassium on serum potassium concentration in hypertensive individuals with normal renal function treated with an ACEi or ARB. We hypothesized that an increase in dietary potassium would not provoke hyperkalemia in this population despite treatment with either an ACEi or ARB. Design: We conducted a controlled, parallel-design clinical trial in 20 hypertensive subjects with normal renal function treated with an ACEi or ARB, with random assignment to a usual diet or a high-potassium diet (HKD). Fruit and vegetable intake was used to increase potassium intake. Serum potassium concentration, 3-d food records, and 24-h urine collections were completed at baseline and 4 wk. Results: In the usual-diet group there were no statistically significant differences for potassium excretion, intake, or serum levels at end of study compared with baseline. The HKD group had significant differences in urinary potassium excretion (83 ± 26 mmol/d at baseline compared with 109 ± 35 mmol/d at 4 wk, P = 0.01) and dietary potassium intake (3775 ± 1189 mg/d at baseline compared with 5212 ± 1295 mg/d at 4 wk, P = 0.02). Despite increased potassium intake in the HKD group, serum potassium concentrations did not significantly increase from baseline at midpoint or end of study (4.1 ± 0.6, 4.3 ± 0.3, and 4.2 ± 0.4 mmol/L, respectively). Conclusion: This study demonstrates that an increase in dietary potassium over a 4-wk period is safe in hypertensive subjects who have normal renal function and are receiving ACEi and/or ARB therapy. This trial was registered at www.clinicaltrials.gov as NCT02759367.